IMPROVING INTENSIVE READING COMPREHENSION THROUGH TASK-BASED LEARNING - Irgasheva, Guzal (Educational Research in Universal Sciences, 2022)
This paper addresses the problem of enhancing one of the challenging skills - intensive reading. In the initial stage, the history of teaching reading skills by professionals are analyzed, their methods and techniques which were implemented through years and their actuality of today’s teaching system. The approach of teaching reading through task-based learning and the importance of intensive reading in today’s education are discussed. We will take a look at historical background of teaching reading. Meanwhile, there is a reading method which is suggested by an author of this paper.